Teaching history with message movies - Carr, Steven Alan, 1964-; Frost, Jennifer, 1961- (Teaching history with . . . series, 2018)
"This volume is a teacher's guide for teaching with "message," or social problem, films. It will cover key themes and concepts and will also provide an era-by-era overview of significant issues and related films, a tutorial in using film in historical methodology, user guides for key movies, and sample exercises and assignments for classroom use"--